Status Gizi, Asupan Fe dan Kepatuhan Konsumsi Tablet Fe pada Ibu Hamil Anemia di Puskesmas Karanganyar Tasikmalaya - Listianasari, Yanita; Nelnovia, Felia (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2024)
Anemia during pregnancy is a major health problem in developing countries with high levels of morbidity in pregnant women. This study aims to determine the nutritional status, Fe intake and compliance with the consumption of Fe tablets in anemic pregnant women at the Karanganyar Tasikmalaya Community Health Center. This type of research is descriptive research with a cross sectional design. The sample of 62 people consisted of 31 anemic pregnant women and 31 non anemic pregnant women. The data collected includes data on the nutritional status of pregnant women, Fe intake of pregnant women and compliance with consuming Fe tablets. The research results showed that the majority of pregnant women’s nutritional status was not KEK (83,9%). The nutritional status of pregnant women is not-anemic, all of them (100%) have a nutritional status that is not KEK. The Fe intake of anemic pregnant women is 100% included in the severe deficit category and the Fe intake of non-anemic pregnant women is 23 people (74,2%) have a severe deficit. Some anemic pregnant women did not comply with taking Fe tablets (64,5%). Pregnant women are not anemic, most of them adhere to taking Fe tablets (61,3%). The conclusion is that the majority of anemic pregnant women have a nutritional status that is not KEK, pregnant women who are not anemic have a nutritional status that is not KEK. All anemic pregnant women have a severe Fe intake deficit, pregnant women who are not anemic have a severe Fe intake deficit. Most anemic pregnant women do not comply with taking Fe tablets, most non anemic pregnant women comply with taking Fe tablets. It is hoped that anemic and non-anemic pregnant women will improve their diet to 3 times a day with a balanced nutritional menu